Metabolic syndrome among Egyptian children with Familial Mediterranean Fever: a case-control study - Shimaa Atef; Huda Marzouk; Mariam Mahmoud El-khity; Hend Mohamed Abu Shady (SpringerOpen, 2024)
Abstract Background Familial Mediterranean fever (FMF) is the most prevalent inherited autoinflammatory disease globally. Metabolic syndrome (MetS) is a cluster of interrelated risk factors; insulin resistance, obesity, dyslipidemia, and hypertension are the main constituents of MetS. Aim This study aimed to investigate components of metabolic syndrome among Egyptian children with FMF during the attack-free period. Patients and methods This is a case-control study that was conducted in the Pediatric Rheumatology Outpatient Clinic and Pediatric Endocrinology Clinic, Children's Hospital, Faculty of Medicine, Cairo University. It was conducted on 40 patients with FMF. The patients included were of both sexes and aged 10 years or older, during the FMF attack-free period; they were compared to 40 apparently healthy age- and sex-matched children as controls. All subjects in this study were subjected to detailed history taking, anthropometric measurements, general and systemic examinations. Laboratory evaluation (at the time of the study) was done at time of study, in the form of CBC with differential, BUN, creatinine, ESR, serum amyloid A, urine analysis, serum insulin, fasting blood glucose, and lipid profile. FMF gene mutations were collected from patients' files. Results The mean ± SD age of FMF patients was 12.65 ± 1.82 (10-17) years, while the mean ± SD age of the control group was 12.6 ± 1.82 (10-16) years. Among FMF patients, 50% were males, and 50% were females (F:M = 1:1), while in the control group, 47.5% were females, and 52.5% were males. All FMF patients were during the attack-free period. There was a statistically significant difference between both groups regarding insulin resistance, being more frequent among the FMF patients' group, with a p-value of 0.025. Conclusion None of our FMF patients met the criteria for the definition of metabolic syndrome, but there was a significant difference between cases and control regarding insulin resistance with higher frequency among FMF patients, probably due to the ongoing subclinical inflammation. This indicates that children with FMF may be at a higher risk of getting metabolic syndrome later on in life.